Visible light assisted photoelectrocatalytic degradation of sugarcane factory wastewater by sprayed CZTS thin films. (December 2017) - Hunge, Y.M.; Mahadik, M.A.; Patil, V.L.; Pawar, A.R.; Gadakh, S.R.; Moholkar, A.V.; Patil, P.S.; Bhosale, C.H.
Abstract: Highly crystalline Cu2 ZnSnS4 (CZTS) thin films have been deposited onto glass and FTO coated glass substrates by simple chemical spray-pyrolysis technique. It is an important material for solar energy conversion through the both photovoltaics and photocatalysis. The effect of substrate temperatures on the physico-chemical properties of the CZTS films is studied. The XRD study shows the formation of single phase CZTS with kesterite structure. FE-SEM analysis reveals nano flakes architecture with pin-hole and crake free surface with more adherent. The film deposited at optimized substrate temperature exhibits optical band gap energy of 1.90 eV, which lies in the visible region of the solar spectrum and useful for photocatalysis application. The photoelectrocatalytic activities of the large surface area (10 × 10 cm 2 ) deposited CZTS thin film photocatalysts were evaluated for the degradation of sugarcane factory wastewater under visible light irradiation. The results show that the CZTS thin film photocatalyst exhibited about 90% degradation of sugar cane factory wastewater. The mineralization of sugarcane factory wastewater is studied by measuring chemical oxygen demand (COD) values. Graphical abstract: Highlights: Photoelectrocatalytic activity of sprayed deposited CZTS thin films. Enhanced photoelectrocatalytic degradation of sugarcane factory wastewater. Reaction kinetics and degradation of pollutants by COD measurement.